ATP Drives Efficient Terpene Biosynthesis in Marine Thraustochytrids - Zhang, Aiqing; Mernitz, Kaya; Wu, Chao; Xiong, Wei; He, Yaodong; Wang, Guangyi; Wang, Xin (mBio, 2021)
Terpenoids are a large class of lipid molecules with important biological functions and diverse industrial and medicinal applications. Metabolic engineering for terpene production has been hindered by the low-flux distribution to its biosynthesis pathway. Understanding carbon flux controlling mechanisms in a tangled metabolic network is an essential question of cell metabolism. Secondary metabolism, such as terpene biosynthesis, has evolved with low carbon flux due to inherent pathway constraints. Thraustochytrids are a group of heterotrophic marine unicellular protists and can accumulate terpenoids under the high-salt conditions in their natural environment. However, the mechanism behind terpene accumulation is not well understood. Here, we show that terpene biosynthesis in Thraustochytrium sp. ATCC 26185 is constrained by local thermodynamics in the mevalonate pathway. Thermodynamic analysis reveals metabolite limitation in the nondecarboxylative Claisen condensation of acetyl-coenzyme A (CoA) to the acetoacetyl-CoA step, catalyzed by the acetyl-CoA acetyltransferase (ACAT). Through a sodium-elicited mechanism, higher respiration leads to increased ATP investment into the mevalonate pathway, providing a strong thermodynamic driving force for enhanced terpene biosynthesis. Proteomic and metabolomic analyses further show that the increased ATP demands are fulfilled by shifting energy generation from carbohydrate to lipid oxidation. This study demonstrates a unique strategy in nature that uses ATP to drive a low-flux metabolic pathway, providing an alternative solution for efficient terpene metabolic engineering. IMPORTANCE Terpenoids are a large class of lipid molecules with important biological functions and diverse industrial and medicinal applications. Metabolic engineering for terpene production has been hindered by the low-flux distribution to its biosynthesis pathway. In practice, a high substrate load is generally required to reach high product titers. Here, we show that mevalonate-derived terpene biosynthesis is constrained by local pathway thermodynamics, which can only be partially relieved by increasing substrate levels. Through comparative omics and biochemical analyses, we discovered a unique mechanism for high terpene accumulation in marine protist thraustochytrids. Through a sodium-induced mechanism, thraustochytrids shift their energy metabolism from carbohydrate to lipid oxidation for enhanced ATP production, providing a strong thermodynamic driving force for efficient terpene biosynthesis. This study reveals an important mechanism in eukaryotes to overcome the thermodynamic constraint in low-flux pathways by increased ATP consumption. Engineering energy metabolism thus provides an important alternative to relieve flux constraints in low-flux and energy-consuming pathways.